The Effect of Organizational Commitment and Work Motivation on Teacher Performance With Job Satisfaction As an Intervening Variable (In Case Study of Sandikta Vocational School, Bekasi City) - Rivano Aprilyansyah; Masydzulhak Djamil (Dinasti International Journal of Management Science, 2023)
Thesis This made For do testing on the population of SMK Sandikta Bekasi teachers regarding commitment in organization as well as motivation they in Work use satisfaction Work as factor or intervening variable . The method used is descriptive quantitative with a sampling technique that provides equal opportunity for each member of the population to be selected as a sample or often called as non-probability sampling . As much 56 teachers working at Sandikta Vocational School, Bekasi City is population used For primary data source. Primary data was collected through observation, distribution of questionnaires, and literature study. The survey results obtained through deployment questionnaire done testing use SmartPLS 3.0; Tested thing includes model measurements, structural measurements, as well hypothesis test. Based on the results of data processing , it can be variables organizational commitment and job satisfaction, work motivation and job satisfaction, organizational commitment and teacher performance, work motivation and teacher performance, and job satisfaction and teacher performance respectively there is connection positive and significant . In addition, the variable job satisfaction is known can play a significant mediating role between organizational commitment on teacher performance and work motivation on teacher performance. Based on findings it is known that teacher at Sandikta Vocational School, Bekasi City think that commitment organization and motivation Work own influence important for satisfaction work .